The Use of Modus Operandi as an Identification Technique in the Investigation of Cash-In-Transit Robbery in Limpopo Province, South Africa (Global Journal of Human-Social Science, 2025)
The aim of this article is to explore the use of modus operandi (MO) as an identification technique in investigating Cash-In-Transit (CIT) robberies in the Limpopo Province of South Africa. The study adopted a qualitative research approach and a case study design. A purposive sampling technique was used to choose 15 participants from three Serious Organised Crime Investigation Units (SOCIU) of the Directorate for Priority Crime Investigation (DPCI). Semi-structured interviews were conducted with 15 investigating officers attached to Polokwane SOCIU, Phalaborwa SOCIU and Musina SOCIU for data collections. Data was analysed through spiral data analysis. The findings of this study show that CIT robbery is a challenging issue in the Limpopo Province of South Africa. Furthermore, the nature and extent to which CIT robbery occurs in South Africa are also outlined in the study, thus making empirical and significant contributions by exploring and describing the MO used by perpetrators in the commission of CIT robberies. Consequently, the study recommendations proffered include that the CIT robbery investigating officers should undergo specialised training; the implementation of MO database; and provision of sufficient resources to DPCI -SOCIU.
Keywords: modus operandi; identification technique; Cash-In-Transit robbery; serious organised crime